1998
DOI: 10.1177/095207679801300206
|View full text |Cite
|
Sign up to set email alerts
|

Lean Supply: a Strategy for Best Value in Local Government Procurement?

Abstract: Developments in government procurement policy and private sector practice towards a more strategic role provide the context for an examination of the proposals on Best Value in local government. Lean supply is proposed as a means of obtaining better value from suppliers and achieving the goals of better quality, more efficient services and continuous improvement. Empirical evidence is presented from a postal survey of local government purchasing officers, interviews with selected respondents and experiments ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…McQuade 77 discussed the organisational transformation brought about by lean thinking in a UK social housing group. Erridge and Murray 78 reported on the application of lean principles to local government procurement processes, using the example of procurement contracts drawn up by Belfast City Council. The authors concluded that 'lean supply' was compatible with the best value approach to procurement, as long as characteristics of lean that are most closely aligned to manufacturing are adapted to fit the culture of local government.…”
Section: Literature Reviewmentioning
confidence: 99%
“…McQuade 77 discussed the organisational transformation brought about by lean thinking in a UK social housing group. Erridge and Murray 78 reported on the application of lean principles to local government procurement processes, using the example of procurement contracts drawn up by Belfast City Council. The authors concluded that 'lean supply' was compatible with the best value approach to procurement, as long as characteristics of lean that are most closely aligned to manufacturing are adapted to fit the culture of local government.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceived private sector best practice (Tummala et al , 2006) can be generalised under the banner of “lean supply” (Lamming (1993). “Lean” as a concept has now been espoused by the NHS Institute for Innovation and Improvement (2009) but its successful application in UK local government was tested and reported on by Erridge and Murray (1998a, b). The local government lean supply model set out by Erridge and Murray suggests good practice includes long‐term contracts, single‐sourcing, two‐stage tendering and the use of e‐procurement to reduce transaction costs.…”
Section: Perceived English Local Government Best Procurement Practicementioning
confidence: 99%
“…Discussion on procurement collaboration is generally concerned with "buyer and seller" vertical collaboration (for example, [1][2][3][4][5]. More recently that discussion has been supplemented with debating the benefits to be gained through horizontal inter-organisational collaboration with others through joining a consortium [6][7][8][9][10][11][12] or inter-organisation collaboration on shared services [13].…”
Section: Introductionmentioning
confidence: 99%